ANALISIS MANAJEMEN KONSTRUKSI DENGAN METODE POAC (PLANNING, ORGANIZING, ACTUATING, CONTROLLING) PADA PROYEK PONDOK PESANTREN AL-AMANAH 4 KOTA SEMARANG - Kuncara, Dana; Hsada, Ibnu Toto; Permata Suwandi, Putri Anggi (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
The success or failure of a project depends on how construction management manages and utilizes available resources, as well as how it handles problems when they arise. With a company or individual that is professional in the field of construction management, project owners will find it easier to manage their projects effectively and efficiently. In this development, there needs to be adequate construction management system management. With this in mind, the researcher conducted a construction management analysis study on the Al-Amanah 4 Islamic Boarding School Development Project in Amanah City. This research aims to identify the factors that affect the performance of construction management, determine the steps that need to be taken to overcome problems that arise, so that the implementation of construction management performance in the project can run smoothly, and analyze the implementation of construction management perfo